2011
DOI: 10.1007/s10554-011-9816-3
|View full text |Cite
|
Sign up to set email alerts
|

Morphology of coronary artery lesions assessed by virtual histology intravascular ultrasound tissue characterization and fractional flow reserve

Abstract: Fractional flow reserve (FFR) is an index of the physiological significance of a coronary stenosis. Patients who have lesions with a FFR of >0.80, even optimally treated with medication, have however a MACE rate ranging from 8 to 21%. Coronary plaques at high risk of rupture and clinical events can be also identified by virtual histology intravascular ultrasound (IVUS-VH) as plaques with high amount of necrotic core (NC) abutting the lumen. Aim of this exploratory study was to investigate whether the geometry … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…However, the majority of the included lesions (89%) were from patients with stable coronary artery disease and this association needs to be verified in a broader spectrum of patients. Additionally, discrepant results were reported in previous studies examining whether plaque characteristics assessed by OCT ( 14 16 ) or VH-IVUS ( 17 20 ) had an impact on coronary hemodynamics. Hence, the association between coronary physiology and OCT/IVUS-defined plaque vulnerability remains elusive and warrants more evidence.…”
Section: Introductionmentioning
confidence: 71%
See 1 more Smart Citation
“…However, the majority of the included lesions (89%) were from patients with stable coronary artery disease and this association needs to be verified in a broader spectrum of patients. Additionally, discrepant results were reported in previous studies examining whether plaque characteristics assessed by OCT ( 14 16 ) or VH-IVUS ( 17 20 ) had an impact on coronary hemodynamics. Hence, the association between coronary physiology and OCT/IVUS-defined plaque vulnerability remains elusive and warrants more evidence.…”
Section: Introductionmentioning
confidence: 71%
“…Several studies have examined the relationship between VH-IVUS-defined plaque features and physiological severity in coronary stenosis; however, their results are inconsistent. Most of the studies suggested that FFR correlated with IVUS-MLA and plaque burden but not with plaque compositions and TCFA ( 17 19 ). Conversely, a recent study by Sezer et al ( 20 ) showed that necrotic volume, TCFA, and positive remodeling may have an impact on the hemodynamic outcome of intermediate lesions.…”
Section: Discussionmentioning
confidence: 99%
“…The vulnerable plaque is characterized by a large lipid necrosis core and a thin fibrous cap formed by macrophage infiltration and it is closely related to cardiovascular events. 12,13) Vulnerable plaques could be identified by noninvasive and invasive methods. As a kind of invasive examination with good penetrability, VH-IVUS could be used to distinguish and measure the content of fibrous, lipid, necrotic, and calcium constituents.…”
Section: Vulnerable Plaque Evaluation With Vh-ivusmentioning
confidence: 99%
“…However, other recent data in small cohorts demonstrate that physiologic lesion assessment with FFR does not correlate beyond plaque burden with plaque composition or lesion phenotype as assessed by VH-IVUS [47]. TCFA + PB ≥70% + MLA ≤4 mm 2 ≤4·0 mm 2 Figure 3 Data from the PROSPECT trial.…”
Section: Radiofrequency Virtual Histology -Vh-ivusmentioning
confidence: 99%